National and Cultural Origins of the Process of Formation of Pupils’ Ethnic Tolerance - Volodymyr Prysakar (Pedagogical Discourse, 2013)
The article reveals the role of the national and cultural values ​​of the Ukranian nation in the process of ethnic tolerance formation. The process of inter-ethnic tolerance education is seen as the formation of human’s  integrative - personal feature based on the cognitive , emotional and assessment , behavior and activity  components. Relying on scientific and  methodical sources and the results of studies conducted by the author  in secondary schools of Khmelnytsky and Chernivtsi regions,  the necessity of focusing of the educational process on the formation of the value sphere of the individual through the use of the capacity of national  cultural values ​​of the people and the development on this basis of positive motifs in  the context of cultures’ dialogue.